Profit Sharing, Credit Market Imperfections and Equilibrium Unemployment - Erkki Koskela; Rune Stenbacka (Institute for the Study of Labor (IZA), 2004)
We investigate the interaction between labour and credit market imperfections for equilibrium unemployment in the presence of profit sharing. In a partial equilibrium with exogenous outside options increased bargaining power of banks has adverse employment effects. In a general equilibrium with endogenous outside options this relationship is frequently reversed; reduced credit market imperfections increase equilibrium unemployment if the labour market imperfections – measured by the bargaining power of trade unions - are sufficiently strong and benefit-replacement ratio high enough. Finally, we show that higher bankruptcy risks increase equilibrium unemployment under similar conditions.
Keywords: G32; J41; J51; 330; wage and loan bargaining; compensation systems; equilibrium unemployment; outside options; Theorie der Arbeitslosigkeit; Gleichgewicht; Tarifliche Gewinnbeteiligung; Kreditmarkt; Unvollkommener Markt; Lohnverhandlungstheorie; Theorie